Catena-Poly[[[diaquahexapyridine-μ-sulfato-dicobalt(II)]-μ-sulfato] tetrahydrate] - Ali, Hapipah Mohd; Ng, S.W.; Puvaneswary, S. (International Union of Crystallography, 2005)
In the crystal structure of the title compound, [Co2(SO 4)2(C5H5N)6(H 2O)2]·4H2O, the sulfate dianion bridges a (C5H5N)4Co unit to a (C5H 5N)2(H2O)2Co unit, forming a chain that runs along the a axis of the monoclinic unit cell. The Co atoms of the units lie on special positions, each of 1̄ site symmetry. Adjacent chains are linked through the uncoordinated water molecules into layers. © 2005 International Union of Crystallography Printed in Great Britain - all rights reserved.